Determination Of Auxotrophic Nature Of The mutant Micrococcus Glutamicus Ab100 - S. GANGULY; A. K. BANIK (International Journal of Pharma and Bio Sciences, 2011)
An experimental study was carried out to investigate the auxotrophic nature of the newly developed mutant Micrococcus glutamicus AB100. To investigate the role of biotin on growth and l-glutamic acid production by this strain, yeast extract from the minimal salt medium was replaced by 0.2 µg/ml of biotin. Biotin (0.2 µg/ml) was proved to be an essential element for growth production was decreased significantly (p<0.01). But excess biotin created over growth, leading to anaerobic condition which could adversely affect l-glutamic acid production. Thus, in this present study, it was proved that this strain a biotin auxotroph.